Are there benefits to having more children for the oldest-old elderly? A longitudinal analysis on successful aging in China. Issue 1 (2nd January 2020) - Weng, Yulei; Li, Dan
ABSTRACT: Perhaps the most significant cultural difference regarding successful aging is that in western countries it is associated with self-sufficiency, while the Chinese focus is on the availability of support from their children. This study uses five waves from the CLHLS to examine the impact of having children on successful aging. Random-intercept Poisson regressions show that having more living children is positively related to successful aging. Co-residence with children does not contribute to better successful aging; but having children living nearby has a positive effect. Therefore, findings from this oldest-old study show that support from children is important in an individual's aging process. Policies should be adjusted to prepare for the future decrease in support from children.